Integrative depiction of the male reproductive system of the commercial purple crab Homalaspis plana (Platyxanthidae): Structure and function - Pardo, Luis M.; Zara, Fernando J. [UNESP]; Riveros, Marcela P.; Paschke, Kurt; Pretterebner, Katrin; Mantelatto, Fernando L. (Wiley, 2019)
The information available on structures and function of reproductive systems are female-biased in many animal groups and crabs are not an exception. However, knowledge about the male reproductive system can help us to understand evolutionary and ecological processes such as the mating system and mating behavior. This study focuses on an integrative description of the principal regions of the male reproductive system of the purple crab, Homalaspis plana, a commercially exploited crab from the southeastern Pacific. For this description a combination of morphological observation, gravimetric records, histological and histochemical techniques and biochemical analysis were used. Also, a gross description of the seminal receptacle of the female was performed. The male reproductive system of H. plana was highly extended and complex, with a great capacity to produce and store spermatophores and secrete, at least, two kinds of seminal fluids. Sperm production, sperm packaging in spermatophores, storage of spermatophores and seminal liquid secretion were functions localized in specific regions. The vasosomatic index was the highest recorded to date in crabs, symptomatic of a high investment in reproduction. All these traits allow identification of H. plana as an internal sperm plug producer, which matches well with the highly extensible seminal receptacle of females. The great quantity of seminal material transferred to females during mating indicates that males may be able to mate only one time in the reproductive season and thus this species could be vulnerable to sperm depletion in males and sperm limitation in females if the fishery substantively reduced the abundance of males in the populations.
Keywords: Brachyura; mating systems; seminal receptacle; sperm plug; vas deferens